The effect of uphill and downhill exercise on soccer player’s leg power - Stanis Krisyanto; Hari Amirullah Rachman (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
The uphill and downhill training method is one of the exercises that must be applied because it is an important component in the success of the soccer game. The objectives were to examine (1) the difference in the effect of uphill and downhill training on leg power, (2) the difference between players with high and low leg strength on leg power; and (3) the interaction between uphill and downhill training with leg strength (high and low) on leg power of football players. This type of research is an experiment with 2 x 2 factorial. The sample of Sleman United football players is 20 players. Leg and back dynamometer and vertical jump instruments. ANOVA data analysis technique α = 0.05. Research result. (1) There is a significant difference between uphill and downhill training on leg power. The results showed that the uphill training group was better than the downhill group. (2) There is a significant difference between the players with large and small leg strength concerning leg power. Players with large limb strength are better than small legs. (3) There is a significant interaction between the training method and leg strength on the leg power of football players. The research results are expected to be a reference in developing and implementing uphill exercises